A Wireless Sensor Network in Precision Agriculture - Xijun Yan; Xiangwei Meng; Yan Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Wireless sensor network has been applied in precision agriculture. This paper takes CC1000 RF as wireless transceiver, MCU MSP430F149 with high performance and Low-Power as the control center of sensor nodes, which can accurately monitor temperature, humidity and light intensity. Meanwhile, choose LM3S6918 which is a high-performance 32-bit ARM and to design sink node. Since the energy of sink node is unlimited, puts forward a new MAC protocol after experimental researches, and gives the specific methods of implementation and deployment. Experiments prove that the WSN has advantages of Lower-Power and stability. It can be competent for monitoring the general agricultural environment. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.869